Therapeutic potential of hUC-MSC secretome preconditioned with IFN-γ and/or TNF-α: An in vitro study on Alzheimer’s neuronal cell models - Widaja, Edhijanto; Pawitan, Jeanne A.; Ramli, Yetty (Narra J, 2025)
Alzheimer's disease is a progressive neurodegenerative disease that is characterized by toxic Amyloid-β (Aβ) plaques and neurofibrillary tangles (NFTs). Treatment options include the use of human umbilical cord mesenchymal stem cell (hUC-MSC)-based therapy. Its secretome contains healing substances such as neprilysin (CD10), which breaks down Aβ42; anti-inflammatory cytokines, which lower inflammation; and growth factors, which promote neuronal regeneration. The aim of this study was to produce hUC-MSC secretomes preconditioned with tumor necrosis factor-alpha (TNF-α) and/or interferon-gamma (IFN-γ) to enhance the secretion of these healing substances. hUC-MSCs were sub-cultured in T-25 flasks at a seeding density of 5×10³ cells/cm² in 10 mL xeno-free medium. hUC-MSCs were preconditioned with TNF-α only, IFN-γ only, and a combination of TNF-α and IFN-γ. This study used 10 ng/mL TNF-α and 20 ng/mL IFN-γ. The secretome was harvested after 48 hours of preconditioning and then filtered through a 0.22 µm filter. In vitro tests were conducted to assess the effects of the secretome on neuronal survival using the neuroblastoma SH-SY5Y cell line. These cells were differentiated with retinoic acid (RA) and then exposed to Aβ42 to mimic Alzheimer's disease neurons. Secretome therapy was applied at concentrations of 5%, 10%, and 20% to evaluate neuroprotective effects. Four types of secretome were tested: unpreconditioned, TNF-α preconditioned, IFN-γ preconditioned, and a combination of TNF-α and IFN-γ. High levels of CD10 (neprilysin) expression were observed in hUC-MSCs treated with IFN-γ and TNF-α, although they did not release sufficient soluble neprilysin (sNEP). Viability results indicated that secretomes preconditioned with IFN-γ at 10% and 20% concentrations provided the highest increase in cell viability after 72 hours post-therapy. The combination of TNF-α and IFN-γ preconditioned secretome exhibited synergistic effects, particularly at 5% and 10% doses at 24- and 72-hours post-therapy. In conclusion, preconditioned hUC-MSC secretome represents a promising therapeutic approach for Alzheimer's disease, as it enhances neuronal cell viability and promotes neuronal regeneration. However, further studies are required to optimize sNEP release and maximize therapeutic efficacy in in vivo models.